At-sea distribution of seabirds and marine mammals around Svalbard, summer 1991 - Joiris, Claude (1996)
At-sea distribution of seabirds and marine mammals was quantitatively determined during the Arctic EPOS cruise of RV Polarstern, from 21 June till 28 July 1991, during 377 half-an-hour counts. Data were expressed as numbers per count and as density, and daily food intake was calculated using allometric equations from literature. Mean densities for the whole expedition were 29 seabirds per km2 (mainly little auk, Alle alle; 8.7, kittiwake, Rissa tridcryla; 8.2, Brunnich's guillemot, Uria lomria; 6.5 and fulmar, Fulmarus glacialis; 3.4), 0.06 pinnipeds, 0.01 cetaceans and 0.002 polar bears. Total food intake by seabirds and marine mammals was 3.9 kg fresh weight km2 per day, with extreme values of 6.6 in the northern west-to-east transect and 2.5 in the Storfjorden. The major ecological influence were fish eaters (1.7), and more especially Brunnich's guilemot (1.2). Geographic differences were also detected; food intake by Brunnich's guillemot represented 62% of total intake in Storfjorden, and by the kittiwake, 45% in the first eastern transect. The first and last transects in the western Barents Sea are described and discussed in more detail. Within different sectors, high concentrations of seabirds were noted, corresponding to hydrological features such as fronts between Atlantic and polar waters, as well as ice edges. Values of seabirds density and food intake are higher than in the Greenland Sea, even than at the biologically very active ice edge there. Figures for pinnepeds and cetaceans are similar; numbers of polar bears were higher around Spitsbergen. SCOPUS: ar.j info:eu-repo/semantics/published